Is NF-κB a useful therapeutic target in rheumatoid arthritis?. (1st November 2002) - Feldmann, M; Andreakos, E; Smith, C; Bondeson, J; Yoshimura, S; Kiriakidis, S; Monaco, C; Gasparini, C; Sacre, S; Lundberg, A; Paleolog, E; Horwood, N J; et al.
Abstract : There is increasing evidence that NF-κB is a major, if not the major transcription factor regulating inflammation and immunity. While this implies that blocking NF-κB might be therapeutically beneficial, it raises clear questions regarding the balance between efficacy and safety. In this brief review we discuss the effects of NF-κB blockade in rheumatoid arthritis, inflammation and immunity, and consider possible therapeutic targets within the NF-κB family.